Aboriginal art - Caruana, Wally (World of art, 1993)
Survey of the work of Australia's indigenous artists which shows how the events of the Dreaming and their significance are embodied in artistic works covering a wide range of media from painting and sculpture to printmaking and textile design. Features numerous colour and black-and-white plates, a bibliography, a list of illustrations, a glossary and an index. The author has been the curator of Aboriginal Art at the Australian National Gallery since 1984.